Penerapan Pendekatan STEM Berbasis Simulasi PhET Untuk Meningkatkan Pemahaman Konsep Fisika Peserta Didik - Mahirah Ulfah Abdi; Mustafa Mustafa; Andi Ulfa Tenri Pada* (JIPI (Jurnal IPA dan Pembelajaran IPA), 2021)
The online learning process creates problems that the practicum cannot be carried out during the online learning process. This problem has an impact on the decline in the level of understanding of students' scientific concepts and process skills. Researchers used a PhET-based STEM approach to overcome these problems. The purpose of this study was to determine the impact of the PhET-based STEM approach in improving students' conceptual understanding of physics subjects at SMA N 5 Banda Aceh. Data collection for this study was conducted in March. Analysis of the data used is a statistical test that is independent-t test. The results show that the use of the PhET-based STEM approach has a very positive impact on improving the understanding of physics concepts that are tested through objective tests. The results of the variable understanding of the concept can be seen from the N-Gain. In the concept understanding variable, the experimental class got a gain value of 0.6 and the control class was 0.5. Both fall into the medium category. So it can be concluded that the PhET-based STEM approach can improve students' conceptual understanding in physics.